Assessment of newborn care corners in selected public health facilities in Bihar - Monika Chauhan; Jyoti Sharma; Preeti Negandhi; Siddharth Reddy; Ghanashyam Sethy; Sutapa B Neogi (Wolters Kluwer Medknow Publications, 2016)
Background: A functional newborn care corner (NBCC) is critical to provide immediate care to newborns including resuscitation, warmth, and initial care to sick newborns. NBCC provides an acceptable environment for all infants at birth, and it is mandatory for all delivery points at all levels in the health system including operation theaters. Objective: The objective of this study was to find the status of availability of NBCCs and service provision in selected public health facilities of Bihar. Methods: A total of 57 NBCCs, having high delivery load (>100 deliveries/month), across 25 high-priority districts in Bihar, were selected purposively in consultation with the State Health Society, Bihar, for the assessment. These facilities were assessed for the availability and/or functioning of infrastructure, equipment maintenance, human resource, supply of drugs and consumables, adherence to protocols, and record keeping. Results: Only 22.8% of the NBCCs were found to be fully functional, majority (68.4%) were partially functional, and 9% were nonfunctional. Thirty-seven (64.9%) NBCCs were located inside the labor room premises. Approximately, one-third of the neonates delivered were kept in NBCCs. Equipment though available lacked the provision of annual maintenance contract. Essential drugs such as adrenaline (24.6%) and Vitamin K injection (42.1%) were not available in many facilities. Only 6.2% of the newborns had low birth weight, indicating underreporting. Majority of the health-care staff available were trained but possessed poor skills. Data recording and reporting was also suboptimal. Conclusion: The network of NBCCs needs to be strengthened across the state and linked with higher facilities to achieve the desired reduction in neonatal morbidity and mortality.